The Essence and Significance of Tax Instruments in Ensuring the Recovery of the Economy of Ukraine - Koliada Tetiana A.; Tokarchuk Olha L. (Bìznes Inform, 2023)
The article is aimed at revealing the essence and significance of tax instruments for implementing the budget policy to ensure the recovery of Ukraine’s economy, also at developing recommendations for improving the efficiency of their use. The article generalizes the theoretical foundations of formation and implementation of budget policy; shortcomings and problems that impede the effective functioning of the tax system are identified; an assessment of the efficiency of the use of various tax instruments that can affect the success of implementation of the budget policy is provided; the directions of improvement of tax instruments of budgetary policy to ensure the recovery of the economy of Ukraine are substantiated. It is proved that in modern conditions the discrepancy between the tax system and the state of the economy becomes a chronic problem that has a negative impact on the balanced budget and macro-financial stability of the country. The tax system is one of the key instruments of the State regulation of the economy, as it defines the rules and mechanisms for collecting taxes, their distribution, use to ensure financing of the State functions as such, and achievement of the goals of socioeconomic development. It is substantiated that owing to changes in economic and social conditions, the tax system may lose its efficiency and adaptability to new challenges. There is a situation when legislation becomes outdated, complex and unable to take into account the current realities of the economy. Also, due to the full-scale war on the territory of Ukraine, the volume of the budget deficit has rapidly increased and a recession in the economy takes place. To overcome these problems, the government needs to develop ways to improve fiscal policy by modernizing tax instruments and assessing their effectiveness and their focus on achieving long-term priorities. Prospect for further research in this direction is to determine the optimal structure of tax revenues to budgets of all levels, taking into account the peculiarities of post-war economic development and assess the impact of using tax instruments on stimulating economic recovery in Ukraine.